“It’s ok to not to be ok” : frames and stigma of mental health issues in user-generated content on Instagram : thematic analysis - Koutola, Siiri (2022)
This study examined mental health related discussion in social media platform Instagram among Finns during mental health day 10 October 2021 and the following day. The aim of the study was to identify how mental health issues are framed in user-generated content on Instagram, and whether the stigma of mental health issues was addressed in the frames. The study was conducted as qualitative research. The data consisted of the Finnish description texts of 100 user-generated Instagram posts that were tagged with #maailmanmielenterveyspäivä, the Finnish version of #worldmentalhealthday. The data was analysed abductively through thematic analysis. The findings suggest 3 main frames and 9 sub-frames of how mental health issues are presented in user-generated content on Instagram. The first frame is a persuasive frame, including sub-frames that persuade individuals with mental health issues, their close ones or decision makers to talk about mental health and take action regarding it. Secondly, the interactive frame suggests that Instagram users utilise the social aspect of the platform when addressing mental health issues on Instagram: by searching peer support, showing gratitude to those who have helped them, and leading by example when talking about stigmatised issues in order to encourage others to do the same. Thirdly, the narrative frame consists of individuals revealing their personal life with causality stories, survival stories and behind the scenes stories that describe everyday life with mental health. All these frames could be identified including aspects of stigma, whether it was in the language use, latent attitudes, or the topic of the post.